The Influence of The Auditor's Skepticism Attitude and Utilization of Information Technology Toward Detection Fraudelent of Financial Statement - Yanti Rufaedah; Sugih Sutrisno Putra; Fatmi Hadiani (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Abstract: This study aims to provide empirical evidence about how big attitudes are Professional Skepticism of Auditors and Utilization of Information Technology affect ability auditors in detecting fraudulent financial statements. Research with this quantitative descriptive method using primary data in the form of a questionnaire as an instrument in data collection. Respondents in this study was selected using the convenience sampling method, because it has been determined by KAP. Questionnaire distributed to 60 auditors from 16 KAPs, but only 51 questionnaires were returned and 46 questionnaires were processed. Data analysis using the PLS Method. The results of the study show that there is an attitude of professional skepticism Auditors and Utilization of Information Technology in KAP Bandung City have a significant positive effect on Detection of Financial Statement Fraud, either partially or simultaneously. Keywords: Auditor Professional Skepticism, Utilization of Information Technology, Fraud Detection Financial statements